GAJI DAN DISIPLIN KERJA SEBAGAI VARIABEL YANG MEMPENGARUHI KINERJA PEGAWAI (Studi Kasus pada Dinas Lingkungan Hidup Kota Mojokerto) - Kasnowo Kasnowo; Badri, Syahrul (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
The success of an organization is strongly influenced by maximum employee performance. Every organization must try to achieve the company’s goals optimally, in improving the performance of employess there are many ways that can be done by the organization such as improving discipline, paying attention to employee salaries and others. The design of this study is descriptive using a quantitative approach. The variables of this study are salary and work discipline as independent variables and performance as the dependent variable. The sample was taken by using the saturated sample technique as many as 80 respondents. Data was taken using a questionnaire instrument and tested with multiple linear tests. The value of R Square, amounting to 0.595 which means that the independent variable in this case the salary and work discipline explains the variation of the dependent variable that is the performance of the Mojokerto City Department of Environment employees at 59,9% and the remaining 40,5% is explained by other variables not examined in this research.